The use of Target Language in a Classroom: Focusing on an Indonesian EFL Teacher - Desi Septiani; Yuyus Saputra; Fuad Abdullah (Siliwangi University, 2021)
The employment of Target Language (hereafter, TL) in English language teaching practices has burgeoned significantly. One of the reasons generating such an issue is the notion of providing students (non-native English students) sufficient exposures of English. Conversely, little is known about how English as the TL is deployed as a medium of instruction and communication among teachers and students, notably in the Indonesian junior high school remains under-researched. Hence, this study aimed at scrutinizing such an investigative issue. The participant was a female English teacher applying English as a medium of communication and instruction in the classroom learning practices. The data were garnered through non-participant observations and analyzed thematically (Braun Clarke, 2006). The findings outlined that utilizing the target language in pre- and post- activities and commanding the student by using the target language become an obvious picture of how the TL is used as a medium of instruction and communication among teachers and students. Pedagogically speaking, encouraging students to communicate in the TL (English) enables them to generate their willingness to communicate in the TL and language awareness of the significance of TL in the classroom learning practices.